Interpretasi Morfostruktural Berdasarkan Citra Digital Elevation Model (DEM) untuk Analisis Hidrogeologi Daerah Timur Gunung Merapi, Kabupaten Boyolali dan Klaten, Provinsi Jawa Tengah - , ERIC ARUNG PATANDIANAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The information about lithology, stratigraphic and morphostructural is very helpful in learning the local hydrogeology system. Digital Elevation Model (DEM) is a kind of information that is very essential for various surface analysis purposes that could be implemented in assisting the future groundwater exploration activity. The usage of spatial analysis in ArcGIS 9.3 is for analyzing the ASTER GDEM v.2 elevation data and the elevation of the springs by choosing the IDW interpolation method, the kriging and spline is done for the purpose of the surface analysis and the groundwater flow analysis by searching the Root Mean Squis Error (RMSE) value. The PCI geomatica 8.2 is for the digitally straightness analysis and the usage of Rockwork v.15 is for the straighten statistic of the research isa. The straightness analysis result is used for the morphostructural interpretation by geology mapping and ground checking from the straightness analysis result to know the influence of geological units and morphostructural units against its hydrogeology system. For the straightness analysis, the spline DEM interpolation result is used because the straighten population is the most, the confidance interval that is smaller and the R-mag value that is bigger while for the groundwater flow analysis the spline interpolation result is used because of its RMSE is smaller. The analysis result from the geology and ground check straightness analysis data noted that the research isa stratigraphy is categorized into the old Mount Merapi Pleistocene ages Formation and divided into three units, that is the Andesite Lava unit, Breccia Lava unit and the Pyroclastic Breccia unit and divided into three active morphostructural units that is controlled by the volcanism activity of the Mount Merapi, that is the volcanic cone unit where the Gobumi Fault appear, volcanic slope unit where there is a Pusong Fault and Tawansari Fault, and the volcanic foot unit where there is a Soka Fault. The geology and morphostructure of the research area affect the hydrogeology system where there is two aquifer system that is confined by the Andesite Lava unit which is the shallow aquifer that formed by the Pyroclastic Breccia unit and the Lava Breccia unit as the aquifer while the lenses layers of fine tuff, coarse tuff and the lapili tuff as the aquitard causing the forming of a multi aquifer system that become thinning out toward the bottom of the topography and become the local groundwater system region and the intermediate groundwater system region. The fault that cut through those aquiver system, forming four springs belt that follow the pattern of the fault and the fracture of the Andesite Lava Unit passing the groundwater in the shallow aquifer and into a second aquifer system which is a type of confined aquifer in which the development of a regional groundwater system region.